Wetlands - Silverman, Buffy (Chicago : Raintree, 2013)
Explores wetland habitats around the world, looking at the plants and animals that live there and the adaptations that help them to survive, and also discusses threats to wetlands, and efforts at preserving this type of habitat.
Includes bibliographical references (p. 31) and index.
4.3
K-3
Keywords: Wetlands -- Juvenile literature; Wetlands; Wetlands